DETERMINING MOMENT OF INERTIA USING A THREE-WIRE PENDULUM: AN IN-DEPTH TUTORIAL - Thomson, Michael (Ayden International Journal of Basic and Applied Sciences, 2024)
The moment of inertia, a fundamental property in physics and engineering, quantifies the resistance of a rigid body to changes in its rotational velocity. A larger moment of inertia signifies greater rotational stability. This concept holds significant importance in engineering applications, where mechanisms like engines employ sizable external wheels to enhance rotational steadiness. The magnitude of moment of inertia hinges on the body's mass, mass distribution, and axis of rotation. For objects with uniform mass distribution and regular shapes, calculating the moment of inertia around a fixed axis is straightforward, based on size and mass measurements. However, irregularly shaped objects with uneven mass distribution necessitate experimental measurements. This paper explores the classical method of utilizing a three-wire pendulum to experimentally determine the moment of inertia. By measuring the torsion period and applying the principles of mechanical energy conservation, this approach offers several advantages, including the use of simple instruments, ease of operation, and high precision.